Exploring the challenges faced by Dutch truck drivers in the era of technological advancement - de Winter, Joost; Driessen, Tom; Dodou, Dimitra; Cannoo, Aschwin (Frontiers in Public Health, 2024)
Despite their important role in the economy, truck drivers face several challenges, including adapting to advancing technology. The current study investigated the occupational experiences of Dutch truck drivers to detect common patterns. A questionnaire was distributed to professional drivers, in order to collect data on public image, traffic safety, work pressure, transport crime, driver shortage, and sector improvements. The findings based on 3708 respondents revealed a general dissatisfaction with the image of the industry and reluctance to recommend the profession. A factor analysis of the questionnaire items identified two primary factors: 'Work Pressure', more common among national drivers, and 'Safety & Security Concerns', more common among international drivers. A ChatGPT-assisted analysis of textbox comments indicated that vehicle technology received mixed feedback, with praise for safety and fuel-saving, but concerns about reliability and intrusiveness. In conclusion, Dutch professional truck drivers indicate a need for industry improvements. While the work pressure for truck drivers in general may not be high relative to certain other occupational groups, truck drivers appear to face a deficit of support and respect.